Penguatan Tata Kelola Desa Digital Melalui Optimalisasi Sistem Informasi Desa (SID) di Desa Anjani - Rusminah HS; Rizalulhuda; Husnul Hatimah; Astry Afriliana; Vika Mustika Putri; Tania Aulina Setiawan; Karmila Junida Urfah; Rohan Jayadi; Lalu Muhammad Noval Adipratama; Dewi Saltika; M Ihsanuddin (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The development of digital technology in the Industrial Revolution 4.0 era requires village governments to adapt in data management and public services. However, many villages, including Anjani Village in Suralaga District, East Lombok, still use manual administration systems, resulting in slow, error-prone services and data-driven planning. This activity aims to strengthen digital village governance by optimizing the Village Information System (SID) with a participatory approach involving BAPEDA, village governments, KKN students, and the community. The activity stages include an initial survey, data collection from 17 hamlets, data processing and standardization according to BAPEDA standards, and input into the OpenSID website. The result is a more accurate, structured, and easily accessible village database, thereby increasing service effectiveness, supporting data-driven planning, and encouraging transparency and accountability in village government.